COMMUNICATIVE TEACHING FOR IMPROVING FUNCTIONAL VOCABULARY IN SLOW LEARNERS - Sher Muhammad Awan, Sajid Manzoor, Gul Niazi Bibi (JIE, 2024)
The primary goal of the research is to determine how communicative language teaching (CLT) affects vocabulary instruction for the early slow learners in Rawalpindi. A quasi-experimental design was used to conduct the experimental investigation on 68 early-grade students from public schools. The participants in the experiment received communicative lessons, and pre- and post-test data were gathered. SPSS was used for the analysis of the data. The results demonstrated that teaching communicative language enhanced vocabulary acquisition for slow learners in early grades, suggesting that communicative language instruction be used to teach vocabulary.